Tests de precipitinas y relaciones serológicas entre especies del género Lepidobatrachus Budgett (Anura, Ceratophrynidae) - Cei, José Miguel Alfredo María (1969)
Striking differences between seroproteins of Lepidobatrachus asper, L. laevis and L. llanensis are stressed by disc electrophoresis, and the albumin-globulin patterns show specific features both in individual and pooled samples of the above mentioned species. Also crossed homo-heterologous precipitin tests point out the specific serological relationships between these forms. Moreover the serological distances between L. asper, L. laevis and L. llanensis are of the same magnitude, but all Lepidobatrachus species lie at the same serological distance from Ceratophrys. The results support the recent taxonomic revision of the genus Lepidobatrachus by Barrio (1968) and may suggest a very early brauching of this Ceratophrydid group.